Vexillary degeneracy loci classes in K-theory and algebraic cobordism. (May 2018) - Hudson, Thomas; Matsumura, Tomoo
Abstract: In this paper, we prove determinantal formulas for the K -theory classes of the structure sheaves of degeneracy loci associated to vexillary permutations in type A . As a consequence we obtain determinantal formulas for Lascoux–Schützenberger's double Grothendieck polynomials associated to vexillary permutations. We also prove a generalization of the formula in algebraic cobordism.